An integrated motivational interviewing and cognitive-behavioural intervention promoting physical activity maintenance for adults with chronic health conditions: A feasibility study. (December 2019) - Scott, Sarah E; Breckon, Jeff D; Copeland, Robert J
Objectives: Physical activity is recommended for managing chronic health conditions but is rarely maintained. This feasibility study aimed to evaluate the preliminary efficacy of a motivational interviewing and cognitive-behavioural intervention for long-term physical activity for adults with chronic health conditions. Methods: Participants ( N = 37) with stable conditions (e.g. diabetes) were randomized into a three-month motivational interviewing and cognitive-behavioural group ( N = 20) or usual care ( N = 17) after completing a physical activity referral scheme. Participants completed physical activity (e.g. average steps per day and kilocalorie expenditure), psychological (e.g. self-efficacy) and epidemiological (e.g. body mass index) standardized measures at baseline, three- and six-month follow-up. Treatment fidelity and feasibility were assessed. Results: Thirty-five participants completed the study (96% retention). The motivational interviewing and cognitive-behavioural group maintained kilocalorie expenditure at three ( p = 0.009) and six months ( p = 0.009). Exercise barrier self-efficacy ( p = 0.03), physical ( p = 0.02) and psychological ( p = 0.01) physical activity experiences were increased at three months only. No difference was found for average steps/day, social support, coping skills and epidemiological factors. Discussion: This is the first study to demonstrate the feasibility and preliminary efficacy of motivational interviewing and cognitive-behavioural interventions for promoting physical activity maintenance in a clinical population. A large-scale trial with a longer follow-up (≥6 months) is warranted with treatment fidelity assessment.